Identification of Bioactive Constituents in Forest Honey Using GC-MS and Anti-Inflammatory Activity Through Protein Denaturation - Hariana, Hariana; Fristiohady, Adryan; Purnama, La Ode Muhammad Julian; Yodha, Agung Wibawa Mahatva; Irnawati, Irnawati; Wahyuni, Wahyuni; Jumriani, Jumriani (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Honey is a natural product rich in bioactive compounds with various pharmacological and anti-inflammatory effects. Bee species and nectar sources influence the composition of bioactive compounds in honey. This study aimed to identify bioactive compounds and evaluate the anti-inflammatory activity of honey from Apis mellifera and Apis dorsata. Compound identification from both honey types was performed using Gas Chromatography-Mass Spectrometry (GC-MS). At the same time, anti-inflammatory activity was assessed through the human red blood cell (HRBC) membrane stabilization method and protein denaturation inhibition assay, with sodium diclofenac as a positive control. GC-MS analysis revealed various bioactive compounds, notably 2-Propenoic acid, 3-(4-methoxyphenyl)-2-ethylhexyl ester, consistently present in both honey types. In the HRBC assay, Apis mellifera honey showed the highest stabilization value of 94.14% at a concentration of 6.25 mg/L honey solution, surpassing sodium diclofenac (87.96%), while Apis dorsata honey reached 85.21%. All samples achieved over 95% stabilization at 100 mg/L. In the protein denaturation assay, Apis dorsata honey exhibited stronger anti-inflammatory potential with an IC₅₀ of 12.85 ± 1.477 mg/L compared to Apis mellifera (25.35 ± 0.024 mg/L). In conclusion, both types of honey possess promising natural anti-inflammatory potential through membrane stabilization and protein protection mechanisms.